Padre - Crisóstomo. Alejo; Maurel, Cesar, 1959-; Schie Soto, Aaron van (Ceibita Films, 2013)
Emilio lives in the countryside, away from the hectic city life. One day he discovers that someone has invaded his land and sets a trap to catch the intruder. Emilio recognizes himself in the visitor and finds in him a part of the life that had been taken from him. --